Prison System of Brazil and the Role of the CNJ in Promoting Human Rights Effectiveness (Research, Society and Development, 2019)
The dynamics of human rights are critically analyzed, based on the Brazilian democratic platform established with the Federal Constitution of 1988. With this, the limits of the democratic regime as a field for the recognition and affirmation of human rights are pointed out. Brazil, in concurrent application with the current criminal legislation. To do so, the investigation starts from the critique of the Human Rights theory in relation to the effectiveness, with regard to criminal policy. As often depicted by the media, human rights are seen as "bandit rights." This misrepresentation is perhaps due to the failure of criminal legislation where human rights, by their very nature, are perhaps better elaborated and defined than Brazilian criminal law. Structural problems may be the answer to such distortion. The CNJ has been carrying out a mobilization work to solve the problem in the Brazilian prisons. In this scenario, in which many believe that Human Rights compromise the efficiency of the criminal, the present work will be carried out by the deductive method, through bibliographical research, scientific articles and specialized periodicals, to identify the true cause of the problem. Therefore, the present work aims to reflect on these aspects and to point out possible solutions for the harmonization of the implementation of human rights in concomitance with the effective application of the sentence. The results obtained in the research demonstrate the need for public policies and restorative justice to raise public awareness about the need for resocialization of the victim and the State guaranteeing the fundamental rights of the victim as an effective way of promoting justice and social welfare.